「アイスランドと欧州統合」：ＥＵ加盟を逡巡してきた小国の軌跡 - 小久保,康之 (東洋英和女学院大学大学院, 2024)
Iceland has kept its distance from European integration. The conservative Independence Party and Progressive Party, which have been in power for many years, have consistently opposed EU membership, citing the need to maintain national sovereignty and protect the traditional industries of fishing and agriculture. However, facing a financial crisis in 2008, a left-wing coalition government in favor of EU membership submitted an application to the EU in 2009. However, when the conservative coalition government came to power again in the 2013 general election, it unilaterally suspended accession negotiations, and the application has been frozen since then. Iceland joined the EEA (European Economic Area) in 1994, securing access to the EU's single market, and is trying to maintain its own economic interests by skillfully using the institutional framework. departmental bulletin paper